Blowup of Smooth Solutions for an Aggregation Equation - Wenxin Yu; Yigang He (Abstract and Applied Analysis)
We study the blowup criterion of smooth solutions for an inviscid aggregation equation in . By means of the losing estimates and the logarithmic Sobolev inequality, we establish an improved blowup criterion of smooth solutions.